(untitled) (The Chittagong University Journal of Science, 2022)
A large market of furniture has developed in Chittagong city within the last two decades. There is no much research work on cross elasticity of demand on wooden furniture of Chittagong city. The study attempts to know the effect of several selected factors on wooden furniture. It accomplishes with a semi-structured questionnaire and collects data from 150 households randomly. It hypothesizes that alternative products to wooden furniture are good substitutes. The study identifies that the wooden furniture as a relatively necessary product has an elasticity measurement of less than 1 concerning the alternative products. The cross elasticity of wooden furniture to its alternative products’ quantity is 0.30012 at a positive relationship (p<0.001), to the price of the alternative products 0.07155 at a negative relationship (p<0.10) and to family size 0.2825 at a positive relationship (p<0.05). Furthermore, regression analysis and elasticity measurement confirm that alternative products to wooden furniture are not substituted goods. Hence, the study nullifies the hypothesis. Again, it signifies that the increase in wooden furniture products’ demand is much higher than the increase in alternative products. Furthermore, it indicates that wooden furniture is luxury goods in some households. The income and quantity demanded of the furniture are comparatively higher in their private apartment than that of the rented apartment. The study will be useful in developing furniture industries in the Chittagong city of Bangladesh. The Chittagong Univ. J. Sci. 43(1): 1-20, 2021